Answer:
x-intercept =
y-intercept =
Explanation:
We are given the following equation of a line and we are to find the x and y intercepts for it:
To find the x-intercept, we will put in 0 for the y to get:
To find the y-intercept, we will put in 0 for the x to get:
So the x-intercept is while the y-intercept is .
To find the intercepts, the other number will be 0 (x-intercept: when y is 0, and vise-versa).
So:
x-intercept: 0 + 1 = 3x - 12 -> 3x = 13 -> x = 13/3, so it will be (, 0).
y-intercept: y + 1 = 3*0 - 12 -> y = -13, so it will be (0, -13).
6.0m questions
7.9m answers